(untitled) (Journal of Hama University, 2022)
The research was conducted on 150 unsexed one-day-old hybrid birds (ROSS308), in order to study the effect of different concentrations of aqueous and alcoholic extract of olive leaves on some productivity indicators of broilers, such as feed consumption rate, live weight and feed conversion factor. The chicks were randomly distributed to Five groups with 30 birds per group and each group contains three replicates. The aqueous extract of olive leaves was added to the drinking water at a dose of extract of 5 g / liter for the first group and 15 g / liter of extract for the second group, respectively. Also, alcoholic extract of olive leaves was added to the drinking water at a dose of extract 5 g / liter for the third group and 15 g / liter of water extract for the fourth group, the experiment lasted 42 days and the feed and water were provided freely .The results of the study showed that there was no significant difference (P<0.05) in feed consumption among the experimental groups, while a significant increase was observed (P<0.05) in the live weight of the fourth group birds (2647.84) compared with the control group (2586.96). Also, there was a non-significant improvement (P<0.05) in the feed conversion factor of the fourth group birds (1.68) compared with the control group. (1.71). We conclude from this study that adding alcoholic extract at a dose of 15 g/L extract led to an obvious improvement in the studied production indicators.